2010
DOI: 10.1182/blood-2009-12-257832
|View full text |Cite
|
Sign up to set email alerts
|

Tissue macrophages act as cellular chaperones for vascular anastomosis downstream of VEGF-mediated endothelial tip cell induction

Abstract: Blood vessel networks expand in a 2-step process that begins with vessel sprouting and is followed by vessel anastomosis. Vessel sprouting is induced by chemotactic gradients of the vascular endothelial growth factor (VEGF), which stimulates tip cell protrusion. Yet it is not known which factors promote the fusion of neighboring tip cells to add new circuits to the existing vessel network. By combining the analysis of mouse mutants defective in macrophage development or VEGF signaling with live imaging in zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

64
919
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 959 publications
(1,008 citation statements)
references
References 55 publications
64
919
3
3
Order By: Relevance
“…Fantin's study elaborately revealed that microglia was in contact with neighbouring endothelial cells and concluded microglia bridging vascular sprouts 21. We also notice microglia BV2 cells residing at the branch point of the tubular‐like structures in vitro and in close proximity to endothelial tip cells of the growing vascular tree in vivo .…”
Section: Discussionmentioning
confidence: 51%
“…Fantin's study elaborately revealed that microglia was in contact with neighbouring endothelial cells and concluded microglia bridging vascular sprouts 21. We also notice microglia BV2 cells residing at the branch point of the tubular‐like structures in vitro and in close proximity to endothelial tip cells of the growing vascular tree in vivo .…”
Section: Discussionmentioning
confidence: 51%
“…Such factors can affect blood vessel development by modifying the extracellular matrix, 15 affecting the growth factor milieu, 16,17 and guiding vessel anastomosis. 18 During wound repair, mice deficient in macrophages have abnormally overgrown vasculature that surprisingly results in enhanced repair rate. 19 One of the mechanisms by which macrophages regulate vessel branching in development involves a noncanonical Wnt-Flt1 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…S5 E and F). All these results suggest that gonadal macrophages are M2-like, a state that is associated with vascular and tissue remodeling (11,36).…”
Section: Fetal Gonadal Macrophages Are M2-like Macrophages In Activementioning
confidence: 90%
“…In contrast to postnatal contexts and disease states, there are few documented examples of the role of macrophages in fetal organogenesis. In the fetal brain, macrophages are involved in anastomosis during vascular remodeling, because they associate with endothelial tip cells to promote the fusion of adjacent vascular branches (36). One previous study reported that latestage E18.5 colony stimulating factor 1 (Csf1)-deficient fetuses, which showed reduced numbers of macrophages, had decreased insulin cell mass and abnormal pancreatic islet morphogenesis (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation